Veggies under cover - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Guide to sheltered vegetable cultivation in the humid Tropics By C Langlais & P Ryckewaert, CIRAD-FHLOR. 2001. 93 pp. ISBN 2 87614 440 9 Euro 15.24